FUM Gene Expression Profile and Fumonisin Production by Fusarium verticillioides Inoculated in Bt and Non-Bt Maize - Rocha, Liliana O.; Barroso, Vinícius M.; Andrade, Ludmila J.; Pereira, Gustavo H. A.; Ferreira-Castro, Fabiane L.; Duarte, Aildson P.; Michelotto, Marcos D.; Correa, Benedito (Frontiers in Microbiology, 2016)
This study aimed to determine the levels of fumonisins produced by F. verticillioides and FUM gene expression on Bt (Bacillus thuringiensis) and non-Bt maize, post harvest, during different periods of incubation. Transgenic hybrids 30F35 YG, 2B710 Hx and their isogenic (30F35 and 2B710) were collected from the field and a subset of 30 samples selected for the experiments. Maize samples were sterilized by gamma radiation at a dose of 20 kGy. Samples were then inoculated with Fusarium verticillioides and analysed under controlled conditions of temperature and relative humidity for fumonisin B1 and B2 (FB¬1 and FB2) production and FUM1, FUM3, FUM6, FUM7, FUM8, FUM13, FUM14, FUM15 and FUM19 expression. 2B710 Hx and 30F35 YG kernel samples were virtually intact when compared to the non-Bt hybrids that came from the field. Statistical analysis showed that FB¬1 production was significantly lower in 30F35 YG and 2B710 Hx than in the 30F35 and 2B710 hybrids (P < 0.05). However, there was no statistical difference for FB2 production (P > 0.05). The kernel injuries observed in the non-Bt samples have possibly facilitated F. verticillioides penetration and promoted FB1 production under controlled conditions. FUM genes were expressed by F. verticillioides in all of the samples. However, there was indication of lower expression of a few FUM genes in the Bt hybrids; and a weak association between FB1 production and the relative expression of some of the FUM genes were observed in the 30F35 YG hybrid.